THE IMPROVEMENT OF ENGLISH PRONUNCIATION THROUGH YOUTUBE VIDEOS - Ariana, Ariana (JKIP (Jurnal Keguruan dan Ilmu Pendidikan), 2015)
The research was aimed at finding out the students’ pronunciation achievement at the second year students of SMK Negeri 1 Limbung by using YouTube Videos, and finding out whether or not using YouTube Videos is effective to improve students’ pronunciation. The design of the research was pre-experimental with one group pre-test and post-test design. It aimed at find out whether YouTube videos developed students’ pronunciation after gave treatments or not. The research applied pre-experimental method, with pre-test and post-test to one experimental group. The population of the research was the second year students of SMK Negeri 1 Limbung in academic year 2014-2015. The XII/A class consists of 15students and XII/B class consist of 20 students. The number of population was 35 students. This research used the purposive sampling technique that is carries out by choosing one class to represent all the population. Class XII/A as sample of the research consists of 15 students. Based on the result of data analysis and the discussion of the result in the previous chapter, the researcher concludes that (1) YouTube Videos gives the students’ achievement in improving pronunciation. It is proven by 53% of improvement which indicates that the mean score of post-test ( ) is higher than the mean score pre-test (52), and (2) YouTube Videos is effective to improve the students’ pronunciation. It is proved by  improvement which indicates that the mean score of post-test ( ) is higher than the mean score of pre-test (52). It also can be seen from the result of t-test is greater (8.5) than t-table (2.14). That means there is the significance different by using YouTube Videos in teaching pronunciation. In the other word there is the improvement of the students’ pronunciation through YouTube Videos in teaching process.